The Impact of Educational Videos and Leaflets on the Use of PPE Among Welding Workshop Employees - Nadapdap, Marshall Jeremia; Silalahi, Marlinang Isabella; Sari, Jessika Miranda (Program Studi Sarjana Kesehatan Masyarakat Universitas Prima Indonesia, 2025)
Welding workers are vulnerable to various accident risks, such as electric shock, fire, and explosion, which can result in serious injury and even death. One of the main causes of work accidents is failure to use personal protective equipment (PPE). This study aimed to analyze the effectiveness of video and leaflet-based counseling methods in improving knowledge, attitudes, and actions related to the use of PPE among welding workshop workers. A quasi-experimental study with a non-randomized pretest-posttest control group design was conducted in Tanjung Gusta Village, Medan, involving 36 welding workshop workers who were divided into intervention (video) and control (leaflet) groups. The results showed that both extension methods significantly improved workers' knowledge, attitude, and action scores (p<0.05). However, video counseling showed a greater advantage, with a higher mean score increase and a significantly higher N-Gain value (61.8) compared to leaflet (43.3) (p<0.001). Mann-Whitney analysis confirmed that the intervention group using the video showed a significant increase in mean knowledge, attitude and action scores compared to the control group. This study concludes that video education is more effective than leaflets in improving PPE use among welding workshop workers. Integration of video-based education into occupational health programs is recommended to improve worker safety behavior.